PROSPEK PEMBELAJARAN AQIDAH AKHLAK MENGGUNAKAN MODEL CONTEXTUAL TEACHING LEARNING DI SEKOLAH DASAR - Zunaidi M Rasid Harahap (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2021)
The purpose of this study was to describe the prospects for learning Aqidah Akhlak through the Contextual Teaching Learning (CTL) model in schools. The research method that has been carried out is descriptive qualitative research method, data is collected using documentation techniques, interview techniques, and observation. The data analysis technique is done by collecting data, reducing data, categorizing the data, describing the research findings, and making conclusions. The results showed that learning Aqidah Akhlak in Al-Islam subjects at SD Muhammadiyah could be done by teachers using the CTL learning model. The learning model with this approach is able to increase students' understanding of the meaning of discussions about belief, faith, morality, and character. With this method the benefits obtained are that students are able to explain, present, read well, memorize, and demonstrate good knowledge and behavior according to learning objectives. The CTL model can be used as an approach to the process of internalizing Islamic values ​​in learning Aqidah Akhlak.